2019
DOI: 10.1002/jcp.29300
|View full text |Cite
|
Sign up to set email alerts
|

Single peptides and combination modalities for triple negative breast cancer

Abstract: Unlike other types of breast cancers (BCs), no specific therapeutic targets have been established for triple negative breast cancer (TNBC). Therefore, chemotherapy and radiotherapy are the only available adjuvant therapeutic choices for TNBC. New emerging reports show that TNBC is associated with higher numbers of intratumoral tumor infiltrating lymphocytes. This is indicative of host anti-TNBC immune surveillance and suggesting that immunotherapy can be considered as a therapeutic approach for TNBC management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 152 publications
(213 reference statements)
0
14
0
Order By: Relevance
“…Compared with other subtypes, TNBC is more immunogenic, which indicates that TNBC might obtain additional benefits from immunotherapy. 24,25 Impassion-130 was the first clinical trial to report the positive results of immunotherapy for TNBC. Atezolizumab, a programmed death-ligand 1 (PD-L1) inhibitor, has been approved as the first option, combined with Nab-paclitaxel, for the treatment of locally advanced or metastatic PD-L1 + TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other subtypes, TNBC is more immunogenic, which indicates that TNBC might obtain additional benefits from immunotherapy. 24,25 Impassion-130 was the first clinical trial to report the positive results of immunotherapy for TNBC. Atezolizumab, a programmed death-ligand 1 (PD-L1) inhibitor, has been approved as the first option, combined with Nab-paclitaxel, for the treatment of locally advanced or metastatic PD-L1 + TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Among all breast cancer subtypes, PD-L1 accounts for 20-50%, and its expression rate in TNBC is relatively high. 148,150,[153][154][155] PD-L1 positivity in immune cells correlates with a favorable prognosis [156][157][158] Stovgaard et al 2021 found that PD-L1 expression was associated with improved survival, perhaps due to the more active immune response of lymphocytes with high PD-L1 expression in the TNBC microenvironment. 159 The pathological complete response rate of TNBC patients with high PD-L1 expression was as high as 44.4%, while that of TNBC patients without PD-L1 positive immune cells was 2.6%.…”
Section: Tnbc With Immune Checkpointmentioning
confidence: 99%
“…showing a significant effect in the treatment of TNBC. 148,150,153,154,165,166 Discussion TNBC is the most aggressive and metastatic subtype of breast cancer with high intrinsic heterogeneity. The lack of estrogen receptor (ER), progesterone receptor (PR), and HER-2 expression means that there are few targeted drugs available to patients with TNBC.…”
Section: Tnbc With Immune Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…TNBC is a potential protagonist of immunotherapy in BC manifested by diverse immune signatures with abundant tumor-infiltrating lymphocytes, multifaceted functional immune factors, and immunosuppressive surveillance ( Razazan and Behravan, 2020 ). EVs function as significant mediators of immune regulation in cancer.…”
Section: Extracellular Vesicles In Triple-negative Breast Cancer Immu...mentioning
confidence: 99%